Systematic review of general practice end-of-life symptom control. Issue 4 (20th January 2018) - Mitchell, Geoffrey K; Senior, Hugh E; Johnson, Claire E; Fallon-Ferguson, Julia; Williams, Briony; Monterosso, Leanne; Rhee, Joel J; McVey, Peta; Grant, Matthew P; Aubin, Michèle; Nwachukwu, Harriet TG; Yates, Patsy M
Abstract : Background: End of life care (EoLC) is a fundamental role of general practice, which will become more important as the population ages. It is essential that general practice's role and performance of at the end of life is understood in order to maximise the skills of the entire workforce. Objective: To provide a comprehensive description of the role and performance of general practitioners (GPs) and general practice nurses (GPNs) in EoLC symptom control. Method: Systematic literature review of papers from 2000 to 2017 were sought from Medline, PsycINFO, Embase, Joanna Briggs Institute and Cochrane databases. Results: From 6209 journal articles, 46 papers reported GP performance in symptom management. There was no reference to the performance of GPNs in any paper identified. Most GPs expressed confidence in identifying EoLC symptoms. However, they reported lack of confidence in providing EoLC at the beginning of their careers, and improvements with time in practice. They perceived emotional support as being the most important aspect of EoLC that they provide, but there were barriers to its provision. GPs felt most comfortable treating pain, and least confident with dyspnoea and depression. Observed pain management was sometimes not optimal. More formal training, particularly in the use of opioids was considered important to improve management of both pain and dyspnoea. Conclusions: It is essential that GPs receive regular education and training, and exposure to EoLC from an early stage in their careers to ensure skill and confidence. Research into the role of GPNs in symptom control needs to occur.